Corporate Social Responsibility for Sustainable Development - Riyat, Sonia (Ushus Journal of Business Management, 2014)
„Sustainability Development‟ has become the most important area of concern for the world. UN Millennium Development Goals and Vision 2050 etc. are mainly showing the concern for a safe future of human life. The only focus on „maximisation of economic goals‟ will certainly lead to a fall in terms of social and environmental values. „Corporate Social Responsibility‟ (CSR) is an essential tool that enforces a company to pay attention towards all the elements of the environment. By paying serious attention towards CSR the corporates can contribute in achieving the objectives of sustainability to a great extent. Followed by the challenges of sustainability, the paper highlights the importance of CSR for sustainable development